BARZANJI SEBAGAI SUATU STRATEGI DAKWAH DI DESA BANRIMANURUNG KECAMATAN BANGKALA BARAT KABUPATEN JENEPONTO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The main problem in this study is How barzanji as a dawah strategy in Banrimanurung Village West Bangkala District Jeneponto Regency?. Based on the subject matter is outlined into two sub-problems, namely: 1) How is the strategy of da'wah pabarzanji in the implementation of barzanji tradition?. 2) What message does da'wah contain in the tradition of barzanji?. The type of research used is qualitative research that uses da'wah approach method and field research approach. The data collection method in this study uses observation methods, documentation interviews and informant determination. Research instruments. Data analysis techniques and processing techniques include data analysis, data reduction, data display, comparison analysis, and conclusion drawing. The results of this study showed that the strategy of da'wah pabarzanji is to wear Muslim clothes, songkok and sarong, give explanation to the community, read the text of barzanji with a beautiful rhythm heard, attend an invitation to read barzanji. And the message of da'wah in the tradition of barzanji is to read shalawat, form morals, tighten silaturahim rope, and charity. Implications of this study, 1. Hope for the pabarzanji teach the younger generation so that barzanji tradition does not stop from them but can be continued by the next generation of young people banrimanurung village. 2. Hope that pabarzanji can give a direct explanation to the community so that the public can understand about barzanji tradition.